″INTERVENSI PEMERINTAH″ ANTARA KEBUTUHAN DAN PENOLAKAN DI BIDANG EKONOMI (JURNAL ECONOMICA : Research of Economic And Economic Education, 2013)
This paper purpose to seek government intervention in economic which is debated in some parties especially entrepreneur. Some of them desire for government intervention and the rest wishes economic runs without intervention. Government intervention becomes the central point in developing countries. In fact, over intervention generate economic distortion. Government role on development and increasing economic growth is the key to welfare. This paper presence classic economic theory that addresses the importances of government intervention in economic and development. It suggests that government intervention gives impact to “bad” economic actors and public sectors will be protected.